Ergonomic Evaluation of Improved Grain Cleaning Technologies - Comparative Study of Traditional and Improved Tools - Rashmi Shukla and S.R.K. Singh, (Indian Journal of Extension Education, 2015)
This study was conducted to assess ergonomic efficiency of improved hanging type cleaner grader. Twenty farmwomenwere selected to assess and compare the impact of improved technologies over traditional one. The physiological cost ofwork and energy expenditure in terms of heart rate, cardiac cost, time required, strokes, output were observed to be lowerwhile performing selected activities with the improved technologies compared to the traditional one. The work outputwas also found higher with all of the improved technologies. The activity was performed with both the traditional methodusing as well as by using Supa, the improved tools. Results of the study showed that the average heart rate and energyexpenditure of the women were reduced significantly while performing the grain cleaning activity with the use ofimproved tool manufactured by CIAE, Bhopal. The use of both the improved tools also led to reduction in the muscularstresses. Further it was observed that work productivity with the improved tool Hanging sieve had significantly improved.It was therefore recommended that women should be motivated to use the improved tools for grain cleaning to minimizehealth hazards.